PENGEMBANGAN ANOTHER WORLD REBORN DENGAN MENGGUNAKAN METODE GAME DEVELOPMENT LIFE CYCLE - Winardy, Enrico; Surasa, Hendra; Zaman, Baizul (KHARISMA Tech, 2025)
Another World Reborn was developed using the Game Development Life Cycle (GDLC) method, which consists of six stages: initiation, pre-production, production, testing, release, and post-release. The initiation stage involved a literature study on RPGs and GDLC, as well as identifying player needs and initial game specifications. In the pre-production stage, a Game Design Document (GDD) was prepared, along with a storyline, character designs, UI sketches, gameplay flowcharts, and the selection of RPG Maker and legal community assets. The production stage included the creation of visual and audio assets, the implementation of turn-based gameplay, a battle system, dialogue writing, and the implementation of UI/UX. Testing was conducted in two stages: an alpha test using the blackbox testing method by an internal team, and a beta test with 15 high school students using the System Usability Scale (SUS). The test results showed that the game had good story and gameplay quality. The game was released in APK format through a personal website. The post-release stage included documentation, feedback collection, and version update plans. This project demonstrated that GDLC is effective in producing engaging and playable educational RPG games.